Advances in Research on Adropin: Potential Implications for Clinical Diagnosis and Possible Treatment – A Mini-Review - Berdowska, Agnieszka; Berdowska, Sylwia (Current Proteomics, 2024)
Adropin is 76-amino acids protein. It was discovered in 2008. Adropin expression was found in the liver, brain, heart, kidneys, pancreas, testis and ovary, umbilical vein, coronary artery endothelial cells, aortic smooth muscle cells and monocytes/macrophages. Adropin is involved in energy balance, and it has an endothelial protective effect. Changes in adropin content have been found in many diseases and disorders, such as obesity, diabetes mellitus type 1 and 2, coronary artery disease, myocardial infarction, rheumatoid arthritis, primary Sjögren's syndrome, multiple sclerosis, nonalcoholic fatty liver disease, polycystic ovary syndrome and preeclampsia. This mini-review focuses on those papers that have potential implications for clinical diagnosis or possible treatment. It can be assumed that adropin can be useful in the diagnosis of certain diseases. It seems to be a promising candidate for the treatment of diabetes, atherosclerosis, polycystic ovary syndrome and diseases of the nervous system associated with cognitive decline.
Keywords: obesity